VALUE FOUNDATIONS OF STUDENT SCIENTIFIC AND INNOVATIVE ACTIVITIES IN REGIONAL UNIVERSITIES - Ivanchenko, Olga S.; Saenko, Lyudmila A.; Lipchanskaya, Irina V.; Bogdanova, Oksana A.; Suhanov, Alexander V.; Zritineva, Elena I. (International Journal of Psychosocial Rehabilitation, 2020)
The study provides analysis of the value bases and prospects for development of scientific and innovative student activities in regional universities. The authors state that students treat scientific and innovative activities as a corridor of opportunities within social and professional career, adopting the image of pragmatic scientist focused on success, prestige and well-being. The paper outlines the paths of development of state regulation system for student scientific and innovative activity in regional universities. Methodological apparatus of research is based on positions of structural-activity, subject-activity, and dispositional approaches. The main conclusions of the study are based on author’s sociological research. From perspective of results of sociological research, the authors conclude that in modern conditions introduction of students to scientific and innovative activities is determined by variable value vector in relation to science. At the same time, perception of science takes place in the context of socially useful results related to self-realization of individual and implementation of his life plans. The analysis indicates that in research and innovation activities of universities, economic rates are higher than social and educational ones. At the same time, in university system there is being formed creativity ideology: university cannot be a structure focused on commercial services; even more - effectiveness of its activities should be evaluated not by the state of the market, but by the groundwork of technological and organizational innovations laid in the university. The scientific novelty of this study lies in idea that the best way to assess the prospects of public administration in this area is to correlate the results of management with expectations of regional community in implementation of innovative projects.